Inhibition Effect of Chitosan Against Bacteria and Fungi Isolated from Rotten Fruits and Vegetables - Komal; Ejaz, Sania; Sultan, Amna; Khan, Wasim; Begum, Syeda Sundas; Rasheed, Shayan; Qadir, Zeeshan; Gul, Fathma; Ali, Mansoor; Maqbool, Saima; Tauqeer ul Haq, Muhammad; Zakir Ullah; et al. (Indus Journal of Bioscience Research, 2025)
This study aimed to isolate bacterial strains from spoiled fruits and vegetables and evaluate their antibacterial, antifungal, and antioxidant activities, along with exploring the potential of chitosan in extending the shelf life of fresh produce. Bacterial isolates were obtained through nutrient agar plates, followed by Gram staining to identify the strains. The bacteria identified were Escherichia coli, Salmonella spp., Staphylococcus aureus, and Bacillus spp. based on their morphological characteristics. The antibacterial activity of these strains was assessed using the agar well diffusion method, revealing varying inhibition zones depending on the bacterial species. The antifungal activity of the isolates was tested against Aspergillus niger, and although no inhibition zones were observed for the bacterial isolates, the standard antifungal agent, Clotrimazole, demonstrated significant inhibition. Antioxidant activity was measured through DPPH and ABTS assays, with fungal strains isolated from cauliflower and orange showing the highest antioxidant potential. Additionally, the use of chitosan on fresh fruits and vegetables resulted in a notable extension of shelf life. Specifically, tomatoes, brinjal, apples, and bananas exhibited significant improvements in shelf life, extending their typical storage duration. These findings suggest that bacterial strains isolated from fruits and vegetables possess diverse bioactivities, with potential applications in food preservation. Furthermore, chitosan proved to be a promising natural agent for enhancing the shelf life of fresh produce. This study provides valuable insights into the biotechnological potential of natural preservatives and microbial isolates in sustainable food preservation practices, highlighting the importance of exploring eco-friendly alternatives to synthetic preservatives. Future research should investigate the synergistic effects of these bacterial strains and chitosan, as well as their mechanisms of action to further optimize their applications in food security and preservation.